The performances of undershot waterwheel with butterfly-shaped blades and the radius of grasshopper's elbow: The utilization efforts for river electrical energy potential - Suhartono, Suhartono; Rudianto, Rahmat; Fatmawati, Sri; Aziz, Saiful (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Based on the amount of discharge or current, the river flows in Central Kalimantan have the potential to produce electrical energy. The purposes of this study were to design an undershot type of floating waterwheel and to test the effective bending angle at the radius of the grasshopper elbow in producing the most optimum power. This research uses experimental methods. The tools used are: mobile phone, multimeter, the gate of light, timer counter, flow rate, and the dimensions of the waterwheel diameter is 6 meters. Grasshopper angles vary from 0°, 30°, 45°, 60o, and 90° with a submerged blade depth of 0.24 m. The results showed that the undershot waterwheel with a flexible pinwheel (like a grasshopper's elbow) produced a faster and more effective rotation than a wheel with a fixed pinwheel and blades. Because the waterwheel has a flexible pinwheel and the butterfly blades experience little resistance when moving in water, the wheel generates more electrical energy than a wheel with fixed pinwheels and blades.At the angle of bending of the radius of the grasshopper blade 30º with the butterfly blade, it produces more optimal electrical energy than angles 0°, 45°, 60o, and 90°. Suggestions for further research are to test the waterwheel in weak and medium current rivers